Cross-Sectional Study on the Anatomy of the Thyroid Gland and It’s Variations In Different Genders - Sindhu K S; Meer Chisthi M, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Anatomical variations of the thyroid gland significantly impact clinical diagnosis and surgical outcomes. This cross-sectional study aimed to evaluate thyroid anatomical variations across different genders. Aim: To assess and compare anatomical variations of the thyroid gland between males and females. Methods: A total of 80 participants (38 males, 42 females) were studied through ultrasonographic evaluations and surgical/autopsy records. Anatomical variations, gland dimensions, and demographic correlations were documented and statistically analyzed. Results: Significant gender differences were noted in the presence of the pyramidal lobe (68.4% males vs. 50.0% females, P=0.024). Males had significantly larger thyroid volumes, lengths, and widths compared to females (P<0.05). Higher BMI correlated significantly with anatomical variations (P=0.001). Conclusion: Significant gender-specific anatomical variations highlight the need for individualized assessment in clinical and surgical thyroid management.